Text and Context in Biblical Interpretation - Nalkara, Benny (Asian Horizons, 2011)
Joseph Pathrapankal, Text and Context in Biblical Interpretation, Thiruvalla: Christava Sahitya Samithi, 2009 (revised edition; first published in 1993). Pages: 240. ISBN 978-81-7821-125-1